2019
DOI: 10.1037/men0000194
|View full text |Cite
|
Sign up to set email alerts
|

Health-seeking behaviors and health information gathering in older Mexican American males.

Abstract: Evidence suggests that men's health disparities are linked to attitudes and beliefs toward health promotion and risk reduction, participation in high-risk behaviors, and limited health care access and utilization influenced by socioeconomic challenges. However, we know less about the specific factors related to health disparities in older Mexican American males. The purpose of this study was to explore the cultural, social, environmental, and gender factors influencing health-seeking behaviors and health infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(85 reference statements)
2
2
0
Order By: Relevance
“…47 Online information has been found to be one of the main external sources that influence individual's risk perceptions. 48 This study confirmed the increased influence of the Internet on older patients' risk perceptions and risk-averse attitude. Various news and events reported on the Internet provide older patients with information about many potential risks.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…47 Online information has been found to be one of the main external sources that influence individual's risk perceptions. 48 This study confirmed the increased influence of the Internet on older patients' risk perceptions and risk-averse attitude. Various news and events reported on the Internet provide older patients with information about many potential risks.…”
Section: Discussionsupporting
confidence: 76%
“…The increasing dissemination of health information via the Internet is sometimes a challenge in Chinese society 47 . Online information has been found to be one of the main external sources that influence individual's risk perceptions 48 . This study confirmed the increased influence of the Internet on older patients' risk perceptions and risk‐averse attitude.…”
Section: Discussionsupporting
confidence: 68%
“…Functional decline [20,34] Vision impairment [47,48] Physical challenges (eg, back pain, knee injury) [32,35,36] Illness conditions Low literacy [49,50] English language literacy [51,52] Basic health knowledge [53,54] Digital literacy [52,55,56] Information literacy [24,33,43] Health literacy [27,57] eHealth literacy Low self-efficacy [18,49,58,59] Low efficacy and anxiety associated with computer use [49,60,61] Low efficacy in reading and learning [62,63] Low efficacy in OHIS a [55,62] Low efficacy in health information evaluation Negative attitudes [39] Attitude toward internet use [42] Attitude toward technology [20,61,64] Privacy concerns Health beliefs [45] External locus of control [31] Fatalistic beliefs…”
Section: Individual Barriersmentioning
confidence: 99%
“…8,9 Older MA men describe MA women as health promoters and primary care providers who influence health-care decision-making. 10 The underuse of health-care services in MA men has been linked to culture and gender role structures. 11 Therefore, the purpose of this systematic integrative review was to determine how gender influences EOL decision-making among older MAs.…”
Section: Introductionmentioning
confidence: 99%